FRACTIONAL PROBLEMS WITH RIGHT-HANDED RIEMANN-LIOUVILLE FRACTIONAL DERIVATIVES - TADEUSZ JANKOWSKI (TASK Quarterly, 2016)
In this paper, we investigate the existence of solutions for advanced fractional differential equations containing the right-handed Riemann-Liouville fractional derivative both with nonlinear boundary conditions and also with initial conditions given at the end point T of interval [0,T]. We use both the method of successive approximations, the Banach fixed point theorem and the monotone iterative technique, as well. Linear problems are also discussed. A few examples illustrate the results.